2006
DOI: 10.1161/01.atv.0000233358.87583.01
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Inhibits Vascular Remodeling Through Suppression of cAMP Response Element Binding Protein Activity

Abstract: Objective-Although accumulating evidences suggest that impaired thyroid function is a risk for ischemic heart disease, the molecular mechanism of anti-atherosclerotic effects of thyroid hormone is poorly defined. We examined whether thyroid hormone affects signaling pathway of angiotensin II (Ang II), which is critically involved in a broad aspect of cardiovascular disease process. Methods and Results-3,3Ј,5-triiodo-L-thyronine (T3) did not show a significant effect on Ang II-induced activation of extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 30 publications
(36 reference statements)
3
26
1
Order By: Relevance
“…The lack of TRE sites on genes associated with NE differentiation and cell invasion can explain the null effect of T3 on the basal expression of these genes, suggesting that T3 acts indirectly in the ISO response. Studies have demonstrated a protein-protein interaction between nuclear thyroid hormone receptors and CREB in the presence of T3 (a T3-TR-CREB complex), reducing the ability of PKA to phosphorylate CREB (29,70). In our study, T3 did not fully prevent the phosphorylation of CREB, suggesting that the antagonistic effect of T3 on the β-adrenergic pathway does not necessarily occur primordially at this level.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The lack of TRE sites on genes associated with NE differentiation and cell invasion can explain the null effect of T3 on the basal expression of these genes, suggesting that T3 acts indirectly in the ISO response. Studies have demonstrated a protein-protein interaction between nuclear thyroid hormone receptors and CREB in the presence of T3 (a T3-TR-CREB complex), reducing the ability of PKA to phosphorylate CREB (29,70). In our study, T3 did not fully prevent the phosphorylation of CREB, suggesting that the antagonistic effect of T3 on the β-adrenergic pathway does not necessarily occur primordially at this level.…”
Section: Discussioncontrasting
confidence: 56%
“…As mentioned before, this unresponsiveness could be related to the dedifferentiated state and/or the invasive capacity of these cells. TRβ1, the nuclear thyroid receptor, has been identified in both LNCaP and DU145 cells (29); however, T3 exerts proliferative effects only in LNCaP cells (27,62). Overall, our data in vitro and in vivo indicate that T3 restrains cancer progression mediated by β-adrenergic receptors in a model of differentiated cancer.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Although adjustment for s-albumin (one of the main transporters of T3 in plasma) did not modify the observed associations, we should acknowledge that fT3 is not tantamount to T3. Several studies have, nevertheless, suggested anti-atherosclerotic effects of fT3 on the vascular bed via its effect on mitochondrial oxidative systems, induction of vasodilatory molecules, inhibition of angiotensin II receptor expression and inhibition of downstream signal transduction, mechanisms all of which do not necessarily involve the inflammatory cascade (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…This study was supported by the grants from the Key Laboratory for Endocrine and Metabolic Diseases of Ministry of Health (1994DP131044), the China National Clinical Research Center for Metabolic Diseases diate cardiovascular outcome variables and systemic hemodynamic factors may also be involved in the relationship between thyroid hormone status and C-IMT. Nevertheless, the exact mechanisms for these associations remain unclear.. Variations in the thyroid hormone status could affect lipoprotein quality and oxidation 25) , vascular remodeling via an effect on local angiotensin signaling 26) , and endothelial function 27) . In experimental models, T3 has important effects on the vascular system, by inducing relaxation of vascular smooth muscle cells through a direct or indirect effect via activation of nitric oxide synthase and inducing adrenomedullin expression in endothelial cells 28) .…”
Section: Acknowledgmentsmentioning
confidence: 99%